2023
DOI: 10.7759/cureus.36143
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Yoga and Meditation for Attention-Deficit/Hyperactivity Disorder in Children

Abstract: With attention-deficit/hyperactivity disorder (ADHD) being a prevalent disorder in childhood, it is essential to acknowledge the different adverse effects the disorder can have on the quality of life in children. Therefore, this systematic review focuses mainly on children. Medical therapy, especially stimulants, can have many side effects. Our systematic review aims to evaluate the potential of other non-medical treatment options for ADHD, such as yoga or meditation. We used PubMed and Google Scholar as datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The appropriate tune-up and control method is selected based on the classification of the disease and then treated with Tiaoxie Yizhi Formula (regulating willpower formula). On the other hand, multiple studies have shown that non-pharmacological treatment methods such as biofeedback therapy and pharmacological treatment, for example, atomoxetine, have good effects in the clinical treatment of ADHD [13][14][15]. However, the effectiveness of these three treatments combined in school-age children with ADHD remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate tune-up and control method is selected based on the classification of the disease and then treated with Tiaoxie Yizhi Formula (regulating willpower formula). On the other hand, multiple studies have shown that non-pharmacological treatment methods such as biofeedback therapy and pharmacological treatment, for example, atomoxetine, have good effects in the clinical treatment of ADHD [13][14][15]. However, the effectiveness of these three treatments combined in school-age children with ADHD remains to be explored.…”
Section: Discussionmentioning
confidence: 99%